2022
DOI: 10.1002/dta.3377
|View full text |Cite
|
Sign up to set email alerts
|

Identification of etazene (etodesnitazene) metabolites in human urine by LC‐HRMS

Abstract: Etazene (or etodesnitazene) is a novel and highly active synthetic opioid belonging to the rapidly evolving and emerging group of "nitazenes." Etazene metabolites were identified through analysis of a human urine sample. The sample was obtained from a 25-year-old man who attempted suicide by taking a new psychoactive substances (NPS) cocktail purchased online and was analyzed by ultrahigh performance liquid chromatography-high-resolution mass spectrometry (UHPLC-HRMS). Etazene metabolites were predicted with B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…However, N -deethyl- O -demethyl-metonitazene was the principal metonitazene metabolite in the present urine sample but was not reported in the metonitazene-positive case series, although the authors identified O -demethyl- and N -deethyl-metonitazene in urine samples (Krotulski et al 2021 ) and N -deethyl- O -isopropyl-isotonitazene was found to be a major isotonitazene metabolite in urine (Krotulski et al 2020 ); however it is not clear whether the metabolite was searched or not, as the methodology for metabolite identification was not fully described. Etodesnitazene in vitro and postmortem blood and urine results were also consistent with a positive urine in a clinical case (Verougstraete et al 2023 ), but they somewhat differ from findings in rat serum and urine, in which hydroxylation and N -oxidation were more abundant, which might be explained by inter-species differences (Grigoryev et al 2023 ). O -glucuronidation following O -dealkylation was a major metabolic transformation for both metonitazene and etodesnitazene in the present study, but phase II metabolites were not searched in previous reports.…”
Section: Discussionsupporting
confidence: 57%
“…However, N -deethyl- O -demethyl-metonitazene was the principal metonitazene metabolite in the present urine sample but was not reported in the metonitazene-positive case series, although the authors identified O -demethyl- and N -deethyl-metonitazene in urine samples (Krotulski et al 2021 ) and N -deethyl- O -isopropyl-isotonitazene was found to be a major isotonitazene metabolite in urine (Krotulski et al 2020 ); however it is not clear whether the metabolite was searched or not, as the methodology for metabolite identification was not fully described. Etodesnitazene in vitro and postmortem blood and urine results were also consistent with a positive urine in a clinical case (Verougstraete et al 2023 ), but they somewhat differ from findings in rat serum and urine, in which hydroxylation and N -oxidation were more abundant, which might be explained by inter-species differences (Grigoryev et al 2023 ). O -glucuronidation following O -dealkylation was a major metabolic transformation for both metonitazene and etodesnitazene in the present study, but phase II metabolites were not searched in previous reports.…”
Section: Discussionsupporting
confidence: 57%